Answer:
Eva swam 400 meters in 1/5 hour. Her average swimming speed was 2000 meters per hour.
Step-by-step explanation:
Eva swam 2/3*600 meters in 1/5 hour. 2/3*600=400. She swam 400 meters in 1/5 hour, which means she swims 5*400 meters in a whole hour. Eva swims 2000 meters per hour.
Which expression is equivalent to (fg)(5)?
A: f(5) x g(5)
B: f(5) + g(5)
C: 5f(5)
D: 5g(5)
Answer:
f(5).g(5)
Step-by-step explanation:
(fg)=(f.g)
this is how it starts: (fg)(X)= f(x) [g(x)]
x=5
f(5).g(X)
Stephen and Bridget are marking exam papers. Each set takes Stephen 71 minutes and Bridget 2 hours. Express the times Stephen and Bridget take as a ratio in its simplest form.
Answer: 1:1.69014084507
Step-by-step explanation:
PLEASE HURRY!!! What is the value of p in the equation?
One-fourth (8 minus 4 p) + 2 p = 12 Here are the answer choices...
–20
–2
5
10
Answer:
10
Step-by-step explanation:
took the test on edge
what are the solutions of x^2-4x-9=29
Answer: x =(4-√168)/2=2-√ 42 = -4.481
x =(4+√168)/2=2+√ 42 = 8.481
Step-by-step explanation:
Answer:
x = -4.48, 8.48 to the nearest hundredth.
Step-by-step explanation:
x^2 - 4x - 9 = 29
Completing the square:
(x - 2)^2 - 4 - 9 = 29
(x - 2)^2 = 29 + 13 = 42
x - 2 = +/-√42
x = 2 +/-√42
x = 8.48, -4.48 .
Prove that
(1 + cot A + tan A) (sin A - cos A) = sin A tan A - cot A cos A
Answer:
see explanation
Step-by-step explanation:
Using the trigonometric identities
tan A = [tex]\frac{sinA}{cosA}[/tex] , cot A = [tex]\frac{cosA}{sinA}[/tex]
Consider the left side
(1 + cotA + tanA)(sinA - cosA)
each term in the second factor is multiplied by each term in the first factor.
1(sinA - cosA) + cotA(sinA - cosA) + tanA(sinA - cosA)
= sinA - cosA + cosA - [tex]\frac{cos^2A}{sinA}[/tex] + [tex]\frac{sin^2A}{cosA}[/tex] - sinA ( collect like terms )
= [tex]\frac{sin^2A}{cosA}[/tex] - [tex]\frac{cos^2A}{sinA}[/tex]
= ( sinA × [tex]\frac{sinA}{cosA}[/tex] ) - ([tex]\frac{cosA}{sinA}[/tex] × cosA )
= sinAtanA - cotAcosA
= right side ⇒ proven
The diagram represents the factorization of a2+8a+12. A 2-column table with 2 rows. First column is labeled a with entries a squared, 2 a. Second column is question mark with entries 6 a, 12. First row is labeled a with entries a squared, 6 a. Second row is labeled 2 with entries 2 a, 12. What is the missing number that will complete the factorization? 6 8 12 24
Answer:
(A)6
Step-by-step explanation:
Given the quadratic expression: [tex]a^2+8a+12[/tex]
We factorize:
[tex]a^2+8a+12=a^2+6a+2a+12\\=a(a+6)+2(a+6)\\=(a+2)(a+6)[/tex]
Therefore, the missing number that will complete the factorization is 6.
Factorizing a² + 8a + 12 into (a + 2)(a + 6), the missing number to complete the factorization is: 6.
What is Factorization?Factorization can be defined as a process of resolving a product into factors.
Thus:
a² + 8a + 12
a² + 6a + 2a + 12
(a² + 6a) + (2a + 12)
a(a + 6) +2(a + 6)
(a + 2)(a + 6)
Therefore, factorizing a² + 8a + 12 into (a + 2)(a + 6), the missing number to complete the factorization is: 6.
Learn more about factorization on:
https://brainly.com/question/25829061
which of the following descriptions represents the transformation shown in the image? part 2b
Answer: b) rotation of 180°, reflection across y-axis
Step-by-step explanation:
The black triangle is in Quadrant IV.
A rotation of 180° will move it to Quadrant II.
The red triangle is in Quadrant I so you must reflect it across the y-axis.
7/10 divided by 2
Please help if available ✌
Answer:
0.35
Step-by-step explanation:
if you divide them together you get 0.35
Can someone plz help me out! With this problem I really need help ASAP! I will mark you as brainiest! Help help ASAP!
Answer:
[tex]h=\frac{1452}{7\pi }[/tex]
Step-by-step explanation:
[tex]84=\pi \left(\frac{7}{11}\right)^2h\\\mathrm{Switch\:sides}\\\pi \left(\frac{7}{11}\right)^2h=84\\\frac{49\pi }{121}h=84\\[/tex]
[tex]\mathrm{Multiply\:both\:sides\:by\:}121\\121\cdot \frac{49\pi }{121}h=84\cdot \:121\\49\pi h=10164\\\mathrm{Divide\:both\:sides\:by\:}49\pi \\\frac{49\pi h}{49\pi }=\frac{10164}{49\pi }\\h=\frac{1452}{7\pi }\\or\\h=66.0266[/tex]
Answer:
h=66
Step-by-step explanation:
84=22/7 *(7/11)^2*h
84=22/7*49/121*h
84=(22*49/7*121) * h ( we simplify by 7 and 11)
84=2*7/11 *h
84=14/11 *h
84=14h/11
:14
6=h/11
h=6*11
h=66
4
3
5
6
Jacob rolls two fair number cubes. Find the probability that the sum of
the numbers he rolls is 8.
A Use the table to find the sample space for
1 2.
rolling a particular sum on two number cubes.
Each cell is the sum of the first number in that
1
row and column.
2
3
B
How many possible outcomes are in the
sample space?
4
5
с
6
Circle the outcomes that give the sum of 8.
D How many ways are there to roll
a sum of 8?
What is the probability of rolling a sum of 8?.
TRY THIS!
Find the probability of each event.
1a. Rolling a sum less than 5.
1b. Rolling a sum of 7 or a sum of 9.
REFLECT
1c. Give an example of an event that is more likely than rolling a sum of 8.
1d. Give an example of an event that is less likely than rolling a sum of 8.
2x^2+14x-36 factored. please and thanks
Answer:
2 (x - 2) (x + 9)
Step-by-step explanation:
Mark brainliest please
Si una persona de lunes a viernes entrena diariamente 1 hora ¿cuanto tiempo debe entrenar el sábado para que el promedio diario de las horas de entrenamiento de los 6 días sea 1,5 horas?
Answer: 4 horas
Step-by-step explanation:
Una semana (de lunes a viernes) contiene 5 días
Si se entrena 1 hora por día:
1 x 5 = 5 horas (total de horas de entrenamiento de lunes a viernes)
Ese total más el número de horas que se entrena el sábado (x) dividido por 6 (numero de días en la semana incluyendo sábado) debe ser igual a el promedio de horas entrenadas en los 6 días (1.5)
(5+x) /6 =1.5
Despajando x:
5+x =1.5 x 6
5+x =9
x =9-5
x = 4 horas
SH
Complete each step in the following solution.
10x + 8 = 3(x - 2)
10x + 8 = 3x
DONE
7x=
DONE
x= -2
Answer: x= -2
Step-by-step explanation: use pemdas
10x + 8 = 3(x - 2) distribuite parenthesis
10x + 8 = 3x - 6
10x + 8 = 3x - 6 add like terms
7x +8= -6 add like terms
7x= -14 divide to get x alone
x= -2
Answer:
x = - 2
Step-by-step explanation:
10x + 8 =3(x-2)
10x + 8 =3x - 6
10x - 3x = - 6 - 8
7x = - 14
7x/7 = -14/7
x = - 2
Evaluate A^2-B^2 for A=3 and B=-4.
Answer:
7
Step-by-step explanation:
3^2 = 9
(-4)^2 = 16
16-9= 7
15. If the point (5,k) lies on the line represented by the equation 2x + y = 9, the value of k is....
C) -1
D) -2
A and B where wrong. 15 points for whomever answers correctly
Answer:
The answer is C.
Step-by-step explanation:
Given that (5,k) lies on the line that has the equation of 2x + y = 9. So in order to find k, you have to substitute the coordinates into the equation :
[tex]2x + y = 9[/tex]
Let x = 5,
Let y = k,
[tex]2(5) + k = 9[/tex]
[tex]10 + k = 9[/tex]
[tex]k = 9 - 10[/tex]
[tex]k = - 1[/tex]
Evaluate the expression shown for x = 9.
Negative StartFraction 5 over 6 EndFraction x + 7
Negative 13 and one-third
Negative one-half
7 and one-third
9 and two-thirds
Answer:
So since the equation is -5/6x+7 we need to plug in equation. So x is equal to 9 we have -45/6x+7. Now we need to simplify. That will give us -7 1/2+7
= - 1/2 So the answer is B
The answer is -1/2
What is expression?An expression in math is a sentence with a minimum of two numbers/variables and at least one math operation in it. Let us understand how to write expressions. A number is 6 more than half the other number, and the other number is x. This statement is written as x/2 + 6 in a mathematical expression.
Given:
-5/6 x+ 7
Now, for x=9
-5/6 * 9 + 7
=-15/2+7
=(-15+14)/2
=-1/2
Learn more about expression here:
https://brainly.com/question/14083225
#SPJ2
I'll send a screenshot of the problem. I'd really like an answer, please do your best!
Answer:
a). $(725 - 22t)
b). $99
Step-by-step explanation:
Expense account of the school has balance after 't' weeks = $(450 - 70t)
And fundraising account has the balance = $(275 + 48t)
a). Total amount in both the accounts after 't' weeks
= $(450 - 70t) + $(275 + 48t)
= $(450 + 275) + $(-70t + 48t)
= $(725 - 22t)
b). Total amount after 8 weeks
= $(725 - 22×8)
= $(275 - 176)
= $99
what is x2 + y2 + 4x - 14y + 37 = in standard form
Steps:
Since there are no like terms. We have to convert the number that is x2 + y2 + 4x - 14y + 37 into standard form. The correct answer will be NaN X 10°
So that is in a standard form.
Answer: NaN X 10
Please mark brainliest
Hope this helps.
Helpppp with this asappp plz❤️
Step-by-step explanation:
1 (b) ( boy, boy), (boy,girl), ( girl,boy ), ( girl, girl )
(c) 4
(d) 2/4 = 1/2
(e) 1/4
2 (a) (1,head), (1,tail), (2,head), (2,tail), (3,head), (3,tail), (4,head), (4,tail)
(b) (A,1) (A,2), (A,3), (B,1), (B,2), (B,3), (C,1), (C,2),
(C,3)
In the picture above, parallel lines p and q are cut by transversal line t. If the measure of angle 1 is 11x+7 and the measure of angle 8 is x+17, then x is equal to _____ and the measure of angle 1 is_____ degrees. The measure of angle 8 is _____ degrees.
Answer:
-11
Step-by-step explanation:
the transformation shown is a rotation
true or false
Answer:
True
Step-by-step explanation:
the area that lies between Z= - 0.42 and Z= 0.42 is
Answer:
the answer is 0.84
Step-by-step explanation:
assume the two numbers are on a number line and take the absolute value of their difference
a cylinder has radius 2cm. the volume of the cylinder is 100cmcubed. work out the height of the cylinder, rounded to 2 decimal places.
Answer: height = 7.96 cm
Step-by-step explanation:
Height = volume / πr^2
h = 100 / π*2^2
h = 7.96 cm
Melanie’s bedroom floor is rectangular in shape and has a width equal to 8x−6 and a length equal to 7x−3. What equation represents the area of the floor?
Select one or more:
a. A=56x2+66x+18
b. A=56x2+18x+18
c. A=56x2−66x+18
d. A=56x2−18x+18
Answer:
C
Step-by-step explanation:
Since the area of a rectangle is the width multiplied by the length, the area of this one would be:
[tex](8x-6)(7x-3)= \\\\56x^2-42x-24x+18=\\\\56x^2-66x+18[/tex]
Therefore, the correct answer is choice C. Hope this helps!
Oliver bought a scarf that costs 8 dollars and a watch that costs 9 dollars. At the counter he received a discount. If he paid only 13 dollars, how many dollars was the discount.
Answer: 4
Step-by-step explanation:8 + 9 = 17 you take what he paid 13 and subtract 13 from 17 and you get 4. 4 is how many dollars off he got.
Write the coefficients of x² in each of the following 1) 2+x²+x 2) 2-x²+x³
Answer:
(1) 1 (2) 0
Step-by-step explanation:
Looking at 1) 2+x²+x;
The coefficient of x is 1 because we see +x in the express which is the same as 1 × x = x.
2) Looking at 2) 2-x²+x³
There is no expression with x but we have x^2 , x^3 . Hence the coefficient of x is 0 because 0×x =0
Answer:
1) 1 and 2) -1
Step-by-step explanation:
1) 2+x²+x
+x² ⇒ coefficient of x² is 12) 2-x²+x³
-x² ⇒ coefficient of x² is -1The sum of the measures of two complementary angles exceeds the difference of their measures by 86. Find the measure of the larger angle.
Use the Factor Theorem to examine the polynomial p(x)=6x4+x3−45x2+26x+24. Which binomial is a factor of p(x)?
2x+3
(3x-2)
(2x-1)
(3x−4)
Answer:
(D) 3x−4
Step-by-step explanation:
Factor Theorem
Given a polynomial P(x) and a linear function x-a, If P(a)=0, then the linear function x-a is a factor of P(a).
In Option A:
[tex]L$inear Function =2x+3\\Set 2x+3=0$\\x=-\frac{3}{2} \\p(x)=6x^4+x^3-45x^2+26x+24\\p(-\frac{3}{2})=6(-\frac{3}{2})^4+(-\frac{3}{2})^3-45(-\frac{3}{2})^2+26(-\frac{3}{2})+24\\\\p(-\frac{3}{2})=-89.25[/tex]
In Option B
[tex]L$inear Function =3x-2\\Set 3x-2=0$\\x=\frac{2}{3} \\p(x)=6x^4+x^3-45x^2+26x+24\\p(\frac{2}{3})=6(\frac{2}{3})^4+(\frac{2}{3})^3-45(\frac{2}{3})^2+26(\frac{2}{3})+24\\\\p(\frac{2}{3})=22.8[/tex]
In Option C
[tex]L$inear Function =2x-1\\Set 2x-1=0$\\x=\frac{1}{2} \\p(x)=6x^4+x^3-45x^2+26x+24\\p(\frac{1}{2} )=6(\frac{1}{2} )^4+(\frac{1}{2} )^3-45(\frac{1}{2} )^2+26(\frac{1}{2} )+24\\\\p(\frac{1}{2} )=26.25[/tex]
In Option D
[tex]L$inear Function =3x-4\\Set 3x-4=0$\\x=\frac{4}{3} \\p(x)=6x^4+x^3-45x^2+26x+24\\p(\frac{4}{3} )=6(\frac{4}{3})^4+(\frac{4}{3} )^3-45(\frac{4}{3} )^2+26(\frac{4}{3})+24\\\\p(\frac{4}{3} )=0[/tex]
We can see that only Option D: 3x−4 gives a result of 0. Therefore, by the factor theorem, it is a factor of the polynomial.
what is the sum of 1/2(4x+4) + (2x+8)
Answer:
4x + 10
Step-by-step explanation:
1/2 x 4x =2x
2x + 2x =4x
1/2 x 4 = 2
2 + 8 = 10 Answer: 4x + 10
Help me!
A spinner can land on either red or blue. You spin the spinner and then roll a six-sided number cube.
What is the sample space of outcomes?
{(R, 1), (R, 2), (R, 3), (R, 4), (R, 5), (R, 6), (B, 1), (B, 2), (B, 3), (B, 4), (B, 5), (B, 6)}
{(R, B), (B, R), (R, 1), (B, 2), (R, 3), (B, 4), (R, 5), (B, 6)}
{BR, 123456}
{1, 2, 3, 4, 5, 6, B, R}
A sample set contains every possible outcome.
The answer would be:
(R, 1), (R, 2), (R, 3), (R, 4), (R, 5), (R, 6), (B, 1), (B, 2), (B, 3), (B, 4), (B, 5), (B, 6)}
The sample space of the outcomes is {(R, 1), (R, 2), (R, 3), (R, 4), (R, 5), (R, 6), (B, 1), (B, 2), (B, 3), (B, 4), (B, 5), (B, 6)}
How to determine the sample spaceThe sample space of the spinner is:
S1 = {R, B}
The sample space of the six-sided number cube is:
S2 = {1,2,3,4,5,6}
When the two sample spaces are merged together, we have:
S = {(R, 1), (R, 2), (R, 3), (R, 4), (R, 5), (R, 6), (B, 1), (B, 2), (B, 3), (B, 4), (B, 5), (B, 6)}
Hence, the sample space of the outcomes is (a)
Read more about sample space at:
https://brainly.com/question/5750471